ปฏิกิริยาไฮโดรจีโนไลซิสของกลีเซอรอลโดยใช้ตัวเร่งปฏิกิริยานิกเกิลโมลิบดินัมฟอสฟอรัส - พงศกร พงษ์เภตรารัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This report aims to convert glycerol, a low-value chemical product, to other more valuable chemical products via hydrogenolysis reaction using sulfided nickel molybdenum as catalyst. Products from the reaction are expected to be propanediols and proponols. Influences of operating parameters were examined such as temperature and pressure. Reaction pathway over nickel molybdenum and performance of nickel molybdenum phosphorus were also examined. The study of reaction pathway found that glycerol proceed hydrogenolysis through dehydration-hydrogenation pathway forming major products which are 1,2-propanediol and 1-propanol The study of influence of operating temperature and pressure found that temperature has a very strong influence over the reaction because dehydration step is endothermic reaction, while the following hydrogenation step is exothermic. Moreover, if operating temperature is too high it will favor side reactions resulting in formation of longer chain oxygenated organic products. So, precise controlling operating temperature is very essential factor. Significant influence of pressure can be observed in hydrogenation step. Performance of NiMoP catalyst is different from NiMo catalyst. NiMoP highly favors formation of 1,2-propanediol compared to NiMo. The difference in product selectivity occurs in dehydration step resulting from difference in acidity properties which are alternated from presence of phosphorus.